2009
DOI: 10.1111/j.1742-7843.2008.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐Regulation of CD40 Gene Expression and Inhibition of Apoptosis with Danshensu in Endothelial Cells

Abstract: Danshen is commonly used in China for the treatment of atherosclerosis-related disorders such as cardiovascular and cerebrovascular diseases. Research shows that it also has immunostimulation properties. The present study evaluates the protective effect of danshensu, an active water-extractable component isolated from danshen, on an endothelial cell line (CRL-1730) treated with hydrogen peroxide (H 2 O 2 ). Danshensu significantly inhibited endothelial cell viability induced by H 2 O 2 . The treatment of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…Inflammation is involved in all stages of the atherosclerosis, including lesion formation and plaque stability [22]. The adhesion of inflammatory cells to the vascular endothelium plays important role in atherogenic processes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is involved in all stages of the atherosclerosis, including lesion formation and plaque stability [22]. The adhesion of inflammatory cells to the vascular endothelium plays important role in atherogenic processes [23].…”
Section: Discussionmentioning
confidence: 99%
“…1. Several experiments have demonstrated biological activities of Danshensu in improving microcirculation, suppressing the formation of reactive oxygen species, inhibiting platelet adhesion and aggregation, protecting myocardium against ischemia, protecting endothelial cells against injury induced by inflammation (Cheng, 2007;Wang et al, 2009;Han et al, 2009;Chan et al, 2004;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown that tanshinol exhibited vasodilatory properties, elevated serum nitric oxide levels and action of endothelial nitric oxide synthase, protected endothelial cells from homocysteine-induced injury and H 2 O 2 -induced apoptosis, and exerted antioxidant effects (Chan et al, 2004;Lam et al, 2007;Zhao et al, 2008;Yang et al, 2009;. Tanshinol also decreased blood pressure in spontaneously hypertensive rats and attenuated cardiac hypertrophy, venular thrombosis, and methionine-induced hyperhomocysteinemia in rats (Cao et al, 2009;Wang et al, 2009;Yang et al, 2010;Tang et al, 2011a,b).…”
Section: Introductionmentioning
confidence: 99%